Adaptor regulation of LFA‐1 signaling in T lymphocyte migration: Potential druggable targets for immunotherapies?. Issue 12 (30th October 2014) - Verma, Navin K.; Kelleher, Dermot
Abstract : The integrin lymphocyte function associated antigen‐1 (LFA‐1) plays a key role in leukocyte trafficking and in adaptive immune responses through interactions with adhesive ligands, such as ICAM‐1. Specific blockade of these interactions has validated LFA‐1 as a therapeutic target in many chronic inflammatory diseases, however LFA‐1 antagonists have not been clinically successful due to the development of a general immunosuppression, causing fatal side effects. Growing evidence has now established that LFA‐1 mediates an array of intracellular signaling pathways by triggering a number of downstream molecules. In this context, a class of multimodular domain‐containing proteins capable of recruiting two or more effector molecules, collectively known as "adaptor proteins, " has emerged as important mediators in LFA‐1 signal transduction. Here, we provide an overview of the adaptor proteins involved in the intracellular signaling cascades by which LFA‐1 regulates T‐cell motility and immune responses. The complexity of the LFA‐1‐associated signaling delineated in this review suggests that it may be an important and challenging focus for future research, enabling the identification of "tunable" targets for the development of immunotherapies.